Review of Lucas Briola, The Eucharistic Vision of Laudato Si': Praise, Conversion, and Integral Ecology - Patrick Nolin (Journal of Moral Theology)
Review of Lucas Briola, _The Eucharistic Vision of_ Laudato Si'_: Praise, Conversion, and Integral Ecology_